Effects of F171 Mutations in the 6′-N-Acetyltransferase Type Ib [AAC(6′)-Ib] Enzyme on Susceptibility to Aminoglycosides - Chavideh, Ramona (American Society for Microbiology, 1999)
Substitutions at position F171 of 6′-N-acetyltransferase type Ib cause variable loss of aminoglycoside resistance, indicating that this residue plays an important role in the structure and/or function of the enzyme.